Studi Kelayakan Usaha Martabak Queen sebagai Strategi Pengembangan Bisnis Kuliner - Vientiany, Dini; Rahmayani, Elysa; Waznah, Faiza Zayani; Harahap, Fatimah Zahra Marahaini (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The culinary business in Indonesia is growing rapidly, driven by the increasing demand for practical and affordable ready-to-eat food. One culinary business that remains highly attractive is the martabak (martabak) business. This study aims to analyze the feasibility of the Martabak Queen business using a business feasibility study approach. The research method used is descriptive research, collecting primary data through a mini-survey using a questionnaire to 50 respondents, and secondary data obtained from direct observation of business activities. The feasibility analysis is conducted based on several key aspects: market and marketing, legal aspects, technical and operational aspects, and management aspects.The research results show that, from a market and marketing perspective, Martabak Queen has a clear target market with a high level of customer satisfaction, particularly regarding taste quality and price. Legally, the business has a Business Identification Number (NIB) and thus meets basic licensing requirements. Technical and operational aspects indicate that the business location, operating hours, and production capacity align with consumer demand patterns. Meanwhile, from a management perspective, the simple organizational structure is deemed effective in supporting smooth business operations. Based on these analysis results, it can be concluded that Martabak Queen is a viable business and has the potential for sustainable development.